2009
DOI: 10.1038/jhg.2009.65
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry informative markers and admixture proportions in northeastern Mexico

Abstract: To investigate the ancestral admixture in the Mestizo population in northeastern Mexico, we genotyped 74 ancestral informative markers (AIMs) and 15 Y-single-nucleotide polymorphisms (Y-SNPs) in 100 individuals. The Native American contribution is 56% (range: 27.4-81.2%), the European contribution is 38% (range: 16.7-70.5%) and the West African contribution is 6%. The results show a higher European contribution than was reported in other similar studies in the country, albeit with a predominant Native American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 29 publications
4
19
0
1
Order By: Relevance
“…The position of Monterrey is probably explained by a higher European ancestry than the rest of Mexican-Mestizo populations, which agrees with the previously reported increasing gradient of European ancestry toward the northern region of the Mexican territory [1,4,14]. Previous ancestry estimates from Monterrey based on single nucleotide polymorphisms of the Y-chromosome (Y-SNPs) are compatible with this interpretation [15]. In fact, additional MDS plots performed online (https://yhrd.org/) verified that Monterrey was closer to the European populations than to the rest of Mexican-…”
Section: Dear Editorsupporting
confidence: 82%
“…The position of Monterrey is probably explained by a higher European ancestry than the rest of Mexican-Mestizo populations, which agrees with the previously reported increasing gradient of European ancestry toward the northern region of the Mexican territory [1,4,14]. Previous ancestry estimates from Monterrey based on single nucleotide polymorphisms of the Y-chromosome (Y-SNPs) are compatible with this interpretation [15]. In fact, additional MDS plots performed online (https://yhrd.org/) verified that Monterrey was closer to the European populations than to the rest of Mexican-…”
Section: Dear Editorsupporting
confidence: 82%
“…13,14 Although the Y-STRs used in human identification have been employed to estimate paternal admixture in different Mexican-Mestizo populations, 15 these markers do not constitute the ideal tool for this purpose. 16 Available estimates based on Y-SNPs have been generated from a small number of populations, such as that of Mexico City, 17 and those of the states of Guerrero, 18 Jalisco 13 and Nuevo Leó n. 19 Moreover, with the exception of the latter report on Nuevo Leó n, the remaining studies were restricted to two or three Y-linked biallelic markers; thus, the wide diversity of paternal lineages evaluated by Y-SNPs is relatively unknown throughout the Mexican territory. In this work, we examined 18 Y-SNPs in order to establish a confident landscape of the paternal ancestry in Mestizo populations from different regions of the country.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that RS1076563, also a DRD2 intron, was associated with smoking in 14 year-olds (Ducci, et al, 2011). Several studies investigated the RS1800498 SNP, also known as Taq1D, as an ancestry marker since it exhibits a significant allelic variety among racial/ethnic groups (Choudhry, et al, 2006;Martinez-Fierro, et al, 2009;Mez, et al, 2009;Saraswathy, et al, 2009). Again linking this genotype to addictive behavior, an association between a haplotype which includes this SNP and alcohol and smoking behavior was identified (Preuss, Zill, Koller, Bondy, & Sokya, 2007).…”
Section: Snp Proxy Search For Rs1116313 Snpmentioning
confidence: 99%